PMM.23 Preventing Pre-eclampsia – Are we there yet?. (9th June 2014) - Moatti, Z; Lawin O'Brien, A; Edelstein, M; Gupta, M
Abstract : Hypertensive disorders of pregnancy are a leading cause of maternal and perinatal morbidity. The first NICE 'Hypertension in Pregnancy' guideline (2010) recommends daily 75 mg aspirin from 12 weeks' gestation for women with one high risk or more than one moderate risk. Aspirin effectively reduces the risk of pre-eclampsia if administered prior to 16 weeks' gestation (RCOG). The aim of our study was to examine implementation of aspirin administration. Women who delivered at Whipps Cross Hospital January–February 2013 and fulfilled NICE criteria for aspirin were recruited. Proportions receiving aspirin in each risk-group were calculated and compared using relative-risk ratios (RR) and 95% confidence-intervals (95% CI). Of 129 patients included, 91(70%) had one high risk-factors for pre-eclampsia, and 40 (31%) had 2 moderate risk-factors. Two patients with both high and moderate risks were considered high-risk for the analysis. 73 (56.3%, 95% CI 47.9–65.2) received aspirin, 37/73 (50.7%, 95% CI 38.9–62.4) before 16 weeks' gestation. 32 (35%) high-risk patients and 6 (16%) moderate-risk patients received aspirin before 16 weeks' gestation. Chronic kidney and autoimmune disease groups were most likely to receive aspirin (100%, RR 1.6, 95% CI 1.6–2.1 and 71%; RR 1.6, 95% CI 1.6–1.9). In the moderate-risks group, patients with BMI > 35 were 66% less likely to receive aspirin (21%, RR 0.34 95% CI 0.13–0.86). To our knowledge, this is the first study of aspirin administration in pregnancy. Compliance with national guidelines for disease-prevention is low, with iniquity among women at risk. Multi-disciplinary and patient education with a community focus, and trust-wide auditing have been implemented.